PENGARUH KERAPATAN SAMPEL CAMPURAN SEKAM DAN DEDAK PADA KOEFISIEN REFLEKSI DAN KOEFISIEN TRANSMISI GELOMBANG KUSTIK - Abdjul, Tirtawaty (Jurnal Sainstek, 2010)
The method used in this study is the experimental method which aims to determine the influence of sample density husk and bran mixture to the coefficient of reflection and transmission coefficients of acoustic waves. The study was conducted at the State University Physics Laboratory using sample Gorontalo husk and bran mixture of different densities of fruit five. The results of data analysis showed that the density of the sample husk and bran mixture of strong influence of the reflection coefficient (r = 0,947 to r = 0,966) and the transmission coefficient (r = -0,962 to r = -0,999). This indicated that, the greater the density of the sample husk and bran mixture, the greater the intensity of the absorption fraction is produced which is statistically the influence level is indicated by the correlation on coefficient value of about r = 0,95 to r = 0,99. Based on the findings above, it can be concluded that the coefficient of reflection and transmission coefficient are influenced by the sample density husk and bran mixture. The greater the density of the sample husk and bran mixture, the greater the intensity of the absorption produced by the sample. Keywords: Density of Sample, Reflection Coefficient, Transmission Coefficient, Waves Acoustics